Cooperação entre firmas localizadas em arranjos produtivos locais (APLs): um estudo nas empresas do vestuário de Londrina (PR) - Souza, Luiz Gustavo Antonio de; da Câmara, Márcia Regina Gabardo; Arbex, Marco Aurélio (Revista Gestão da Produção Operações e Sistemas, 2006)
Local Productive Arrangements (LPAs) have been considered regional development instruments, once thecooperation among companies and other agents is one of the elements that contribute to their success. Thispaper discusses a textile-clothing chain LPA in the Metropolitan Region in the city of Londrina, Brazil, focusingon their cooperation. In order to identify the agglomeration, the RAIS (Annual Report of social Information)database was used, including the calculation of the locational quotient. In order to evaluate its degree ofdevelopment, some information on the local environment was obtained, and a questionnaire directed to 40companies of the clothing sector in Londrina was applied. It was evidenced that there is an agglomeration ofthe sector there, and that the environment is developed. However, the connections among the companies andthe other agents are incipient, obstructing the cooperation and the dissemination of knowledge and innovation.It is concluded that the region has an informal agglomeration, and it carries enough potential to become anorganized LPA.Keywords: Local productive arrangement; Confidence; Cooperation.